ERECTA and BAK1 Receptor Like Kinases Interact to Regulate Immune Responses in Arabidopsis - Jordá, Lucía; Sopeña-Torres, Sara; Escudero, Viviana; Nuñez-Corcuera, Beatriz; Delgado-Cerezo, Magdalena; Torii, Keiko U.; Molina, Antonio (Frontiers in Plant Science, 2016)
ERECTA (ER) receptor-like kinase (RLK) regulates Arabidopsis thaliana organ growth, and inflorescence and stomatal development by interacting with the ER family (ERf) paralogs, ER-like 1 (ERL1) and ERL2, and the receptor-like protein (RLP) TOO MANY MOUTHS (TMM). ER also controls immune responses and resistance to pathogens such as the bacterium Pseudomonas syringae pv. tomato DC3000 (Pto) and the necrotrophic fungus Plectosphaerella cucumerina BMM (PcBMM). We found that er null-mutant plants overexpressing an ER dominant-negative version lacking the cytoplasmic kinase domain (ERΔK) showed an enhanced susceptibility to PcBMM, suggesting that ERΔK associates and forms inactive complexes with additional RLKs/RLPs required for PcBMM resistance. Genetic analyses demonstrated that ER acts in a combinatorial specific manner with ERL1, ERL2 and TMM to control PcBMM resistance. Moreover, BAK1 (BRASSINOSTEROID INSENSITIVE 1–associated kinase 1) RLK, which together with ERf/TMM regulates stomatal patterning and resistance to Pto, was also found to have an unequal contribution with ER in regulating immune responses and resistance to PcBMM. Co-immunoprecipitation experiments in Nicotiana benthamiana further demonstrated BAK1-ER protein interaction. The secreted Epidermal Pattern Factor peptides (EPF1 and EPF2), which are perceived by ERf members to specify stomatal patterning, do not seem to regulate ER-mediated immunity to PcBMM, since their inducible overexpression in Arabidopsis thaliana did not impact on PcBMM resistance. Our results indicate that the multiproteic receptorsome formed by ERf, TMM and BAK1 modulates Arabidopsis thaliana resistance to PcBMM, and suggest that the cues underlying ERf/TMM/BAK1-mediated immune responses are distinct from those regulating stomatal pattering.